Differences in muscle cross-sectional area and strength between elite senior and college Olympic weight lifters - Funato, K.; Kanehisa, H.; Fukunaga, T. (The Journal of Sports Medicine and Physical Fitness, 2000)
The purpose of this study was to investigate the profiles of muscle cross-sectional area (CSA) and strength capability in relation to lifting ability in Olympic weight lifters. METHODS: The subjects were 8 elite senior lifters (ESL, age=25.2+/-1.3 years, height=1.64+/-0.03 m, mass=68.6+/-4.2 kg, mean+/-SEM) and 9 college lifters (CL, 20.8+/-0.3 years, 1.67+/-0.03 m, 70.53.4 kg) whose predetermined weight classes were within the same range. The CSAs of elbow or knee extensor and elbow or knee flexor muscles were measured using a B-mode ultrasound apparatus. Concentric and eccentric maximal voluntary forces were determined with an isokinetic dynamometer at a constant velocity of 1.05 rad/sec. RESULTS: The best score of the total mass lifted in the snatch and the clean and jerk lifts was significantly higher in ESL than in CL even in terms of per unit of fat-free mass. There were no significant differences between the two groups in fat-free mass, muscle CSA and force values with the exception that ESL compared to CL showed significantly greater force in concentric knee flexion. However, the ratios of force to muscle CSA (F/CSAs) in concentric and eccentric elbow extensions, eccentric knee extension and concentric knee flexion were significantly higher in ESL than in CL. CONCLUSIONS: The present results indicated that the magnitude of muscular development in limbs was similar in elite senior and college lifters whose predetermined weight classes were within the same range. As compared to college lifters, however, elite senior lifters had a higher F/CSA in specific muscle action modes, which might relate to the optimal execution of the Olympic lifts.